3D nonlinear dynamic analysis of cable-moored offshore structures. (1st October 2020) - Wang, Kun; Er, Guo-Kang; Zhu, Zhihui
Abstract: The nonlinear oscillations of the floating structures anchored by cables are studied in three dimensions. The floating structure is anchored by four symmetric mooring lines and the mooring lines are fixed on the seafloor at the other ends. The stiffness matrix of 3D cable element has been established and applied to analyze the dynamics of the 3D floating structures anchored by cables. The complex compatibility conditions which relate the responses of the floating body and cables have been proposed. The equations of motion for the mooring lines and floating body are individually formulated. Then they are combined as an entire system by utilizing the compatibility conditions. At last, the entire system is analyzed numerically with horizontal harmonic excitations applied on the floating body. The amplitudes for both the responses of the platform and the maximum mooring force are studied as the excitation frequency changes. The responses of the platform and the maximum mooring force are also investigated for varieties of cable parameters. Highlights: The 3D cable element is formulated based on the extended Hamilton principle. The nonlinear equations of motions of the cables and floating body are formulated. The equations of motions of the entire system are got by compatibility conditions. The responses and behaviors of the 3D moored floating structures are analyzed.